2019
DOI: 10.1016/j.ypmed.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal BMI, gestational weight gain, and breastfeeding on early childhood weight: Analysis of a statewide WIC dataset

Abstract: •Pre-pregnancy BMI and gestational weight gain contribute to offspring obesity risk. •Breastfeeding does not protect against the effects of these weight-related factors. •Low-income maternal-child dyads are vulnerable to obesity and its health effects. •Providers must find tailored ways to promote healthy weight among these mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Child growth is complexly regulated, with genetic, epigenetic and environmental components having an effect. Increasing maternal and paternal height, weight and BMI are positively correlated with child growth, with especially maternal obesity associating strongly with childhood obesity of the offspring (Addo et al, 2013;Sørensen et al, 2016;Ohlendorf et al, 2019). Furthermore, excessive maternal gestational weight gain and gestational diabetes increase the risk of childhood obesity (Josey et al 2019;Ohlendorf et al, 2019).…”
mentioning
confidence: 99%
“…Child growth is complexly regulated, with genetic, epigenetic and environmental components having an effect. Increasing maternal and paternal height, weight and BMI are positively correlated with child growth, with especially maternal obesity associating strongly with childhood obesity of the offspring (Addo et al, 2013;Sørensen et al, 2016;Ohlendorf et al, 2019). Furthermore, excessive maternal gestational weight gain and gestational diabetes increase the risk of childhood obesity (Josey et al 2019;Ohlendorf et al, 2019).…”
mentioning
confidence: 99%
“…Multiple studies have shown higher pre-pregnancy BMI and significant gestational weight gain correlates with an increased risk of obesity in children [18][19][20]. One particular study analyzed data from the Supplemental Nutrition Assistance Program (SNAP) in Wisconsin and found that for every 1 kg/m 2 increase in pre-pregnancy BMI, there was a 4.5% increase risk of obesity when compared to mothers with normal BMI [21]. Another study showed mothers who underwent Roux-en-Y gastric bypass (RYGB) surgery prior to pregnancy were less likely to deliver a large-for-gestationalage (LGA) child in comparison to mother's with obesity [22].…”
Section: Prenatal Factorsmentioning
confidence: 99%
“…Significant maternal weight gain during pregnancy can increase a child’s risk for obesity. 8,9 There is evidence that increases in BMI percentile level or BMI trajectory in children during the first 3 years of life is predictive of obesity. 10 Infants can develop obesity due to being overfed (such as for comfort) and other feeding practices like bottle feeding in infancy.…”
Section: Screening and Early Identification For Obesity And Associatementioning
confidence: 99%